The role of temporal distance of the events on the spatiotemporal dynamics of mental time travel to one’s personal past and future - I. Colás-Blanco; J. Mioche; V. La Corte; P. Piolino (Scientific Reports, 2022)
Abstract Mental time travel to personal past and future events shows remarkable cognitive and neural similarities. Both temporalities seem to rely on the same core network involving episodic binding and monitoring processes. However, it is still unclear in what way the temporal distance of the simulated events modulates the recruitment of this network when mental time-travelling to the past and the future. The present study explored the electrophysiological correlates of remembering and imagining personal events at two temporal distances from the present moment (near and far). Temporal distance modulated the late parietal component (LPC) and the late frontal effect (LFE), respectively involved in episodic and monitoring processes. Interestingly, temporal distance modulations differed in the past and future event simulation, suggesting greater episodic processing for near as opposed to far future situations (with no differences on near and far past), and the implementation of greater post-simulation monitoring processes for near past as compared to far past events (with high demands on both near and far future). These findings show that both past and future event simulations are affected by the temporal distance of the events, although not exactly in a mirrored way. They are discussed according to the increasing role of semantic memory in episodic mental time travel to farther temporal distances from the present.